Psychological Stress and Coping Strategies in Adolescent Athletes - Ulfa Gayanov; Yashinta Sari Pratiwi; Elyn Arlinda (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study was conducted to explore the types of psychological stress faced by adolescent athletes, examine the coping strategies they implement to manage these stresses, and explain the contribution of social support in maintaining their mental well-being. This study uses a descriptive qualitative design using a single case study approach. The participant was a 16 year old teenager who was actively involved in badminton as a competitive athlete. The selection of participants was determined through purposive sampling based on criteria that were in line with the research objectives. Data collection was carried out through in-depth interviews and participatory observations. The collected data was analyzed using an interactive analysis model developed by Miles and Huberman, which consisted of data reduction, data display, and conclusion drawing accompanied by verification. The findings showed that participants psychological stress was affected by demanding training routines combined with academic responsibilities, inadequate emotional support from parents due to their work commitments, and experiences of social isolation due to limited social interaction outside the context of sport. To cope with pressure, subjects applied emotion-focused coping by setting a study schedule and seeking help from friends when experiencing academic difficulties. Research findings show that social support from family, peers, school, and coaches plays and important role in helping adolescent athletes manage stress and maintain their psychological well being.